Polybenzimidazole nanofibers for neural stem cell culture. (December 2019) - Garrudo, F.F.F.; Udangawa, R.N.; Hoffman, P.R.; Sordini, L.; Chapman, C.A.; Mikael, P.E.; Ferreira, F.A.; Silva, J.C.; Rodrigues, C.A.V.; Cabral, J.M.S.; Morgado, J.M.F.; Ferreira, F.C.; et al.
Abstract: Neurodegenerative diseases compromise the quality of life of an increasing number of people in the world's aging population. While diagnosis is possible, no effective treatments are available. Strong efforts are needed to develop new therapeutic approaches, namely, in the areas of tissue engineering and deep brain stimulation. Conductive polymers are the ideal material for these applications owing to the positive effect of conducting electricity on the neural cell's differentiation profile. This novel study assessed the biocompatibility of polybenzimidazole (PBI) as electrospun fibers and after being doped with different acids. First, doped films of PBI were used to characterize the materials' contact angle and electroconductivity. After this, fibers were electrospun and characterized by scanning electron microscopy, Fourier-transform infrared spectroscopy, and thermogravimetric analysis. Neural stem cell (NSC) proliferation was assessed, and their growth rate and morphology on different samples were determined. Differentiation of NSCs on PBI-β-camphorsulfonic acid (CSA) fibers was also investigated, and gene expression (SOX2, NES, GFAP, and Tuj1) was assessed through immunochemistry and quantitative real-time polymerase chain reaction. All the samples tested were able to support NSC proliferation without significant changes on the cell's typical morphology. Successful differentiation of NSCs toward neural cells on PBI-CSA fibers was also achieved. This promising PBI fibrous scaffold material is envisioned to be used in neural cell engineering applications, including scaffolds and in vitro models for drug screening and electrodes. Highlights: Polybenzimidazole (PBI) was electrospun and doped with different acids. Doping PBI was confirmed by Fourier-transform infrared spectroscopy, thermogravimetric analysis, and electroconductivity changes. Neural stem cells can adhere and grow on all PBI fibers. Doped fibers supported neural stem cell differentiation into neurons and astrocytes.